Maple Wood Heirlooms and the Re-formation of a Dynastic Identity: Elector John of Saxony’s Sermon Notes as Grapho-Relics - Gehrt, Daniel (Renaissance and Reformation / Renaissance et Réforme, 2021)
The widespread practice of taking notes on sermons as a form of learning and piety among literate Protestants in the sixteenth century has been largely untreated by scholars. This article offers a brief survey of this phenomenon before focusing on two eight-piece sets of palm-sized maple tablets that Elector John of Saxony used for taking such notes. While research into these rare objects has tended to concentrate almost exclusively on their textual content, this contribution seeks new insights into these tablets by applying methods common to material culture studies. This approach proves to be useful not only for exploring the tablets’ practical features but also for understanding their significance as the earliest surviving tangible expressions of Lutheran piety originating from a Saxon prince. Elector John’s successors regarded these simple objects as “grapho-relics,” elevating them to family heirlooms that symbolized the redefinition of the dynastic identity of the Ernestine Saxon house as the guardian of Luther and his legacy.